Ndoxoza mphini wumbi! - Saki, Sandile Dudu (Rhodes University, Faculty of Humanities, School of Languages, 2019)
My English half-thesis comprises semi-autobiographical short stories based on my own lived and observed experiences of patriarchal township life, but told through the eyes of others, often those who find themselves victims of societal ills and cruel injustices. The stories deal with issues ranging from rape culture, intimate femicide, social patriarchy and the vulnerability of women, children and people living with disabilities in such settings. Refusing didacticism, I seek to voice the complexity, bravery and beauty of my characters. I draw influence from Joel Matlou's simple narration of the small details of daily life, Can Themba's ability to find humour in the everyday, Chimamanda Ngozi Adichie's contemporary sass and Irenosen Okojie's unconventional, subtle and deeply enigmatic approach to storytelling.,Le thisisi yingqokelela yemibongo enesingqi nefuthe endilincance kubabhali endihlangene nabo kwezi zifundo endingabala kubo uMxolisi Nyezwa, Rustum Kozain nabanye. Injongo yale thisisi kukonwabisa; ukucebisa mhlawumbi ukuthungulula iintongo emva kobentlombe. Maxa wambi ikukukhahlela nakwabo baye banegalelo kwizinto-yinto zokuhlala ngakumbi iimvumi zikaMasikhandi ezifana noMlindelwa 'Inkunz' emdaka' Mralatya owaziwa njengovulindlela kaMasikhandi kwisizwe sakwaXhosa siphela. Bakho ke ababhali abasingqi sabo sindithimbileyo, naba bugcisa ndibuthandileyo endingabalula kubo uMzwandile Matiwana, M. S. Mlandu, Fundile Majola, John Solilo, J. J. R Jolobe kunye noS. E. K. Mqhayi. Liyavakala ifuthe labo kule mibongo, ngakumbi isingqi nokusetyenziswa kolwimi.,English and Xhosa versions provided for dual language submission
Keywords: South African fiction (English)